2017
DOI: 10.1002/epi4.12075
|View full text |Cite
|
Sign up to set email alerts
|

Seizures, electroencephalographic abnormalities, and outcome of ischemic stroke patients

Abstract: SummaryObjectiveSeizures and electroencephalographic (EEG) abnormalities have been associated with unfavorable stroke functional outcome. However, this association may depend on clinical and imaging stroke severity. We set out to analyze whether epileptic seizures and early EEG abnormalities are predictors of stroke outcome after adjustment for age and clinical/imaging infarct severity.MethodsA prospective study was made on consecutive and previously independent acute stroke patients with a National Institutes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 42 publications
1
48
2
1
Order By: Relevance
“…These data add a neurophysiological risk factor to poststroke seizures, reflecting not only their association with large and disabling ischemic strokes but also the importance of EEG for brain functional assessment. In fact, recently, first EEG asymmetry was also reported as an independent predictor of unfavorable stroke functional outcome, even when adjusted for age and clinical and imaging stroke severity …”
Section: Discussionmentioning
confidence: 89%
“…These data add a neurophysiological risk factor to poststroke seizures, reflecting not only their association with large and disabling ischemic strokes but also the importance of EEG for brain functional assessment. In fact, recently, first EEG asymmetry was also reported as an independent predictor of unfavorable stroke functional outcome, even when adjusted for age and clinical and imaging stroke severity …”
Section: Discussionmentioning
confidence: 89%
“…Using DeLong tests, the outcome prediction model including the qEEG index with highest cvAUCs was compared with the model including exclusively known stroke outcome predictors, as well as with models using known predictors and visual EEG analysis variables, namely background activity asymmetry. EEG background asymmetry was chosen in accordance to a previous report where it was shown that this was the variable more strongly associated with anterior circulation ischaemic stroke outcome (Bentes et al, 2017c). Cut-off values were calculated for various sensitivities and specificities.…”
Section: Resultsmentioning
confidence: 99%
“…The global aim of this thesis was to use the clinical model of acute ischemic cerebrovascular disease to study the value of EEG in the differential diagnosis of transient neurological symptoms, in the diagnosis and prediction of poststroke seizures and epilepsy, as well as to analyze if electroencephalographic abnormalities and/or epileptic seizures are independent predictors of an anterior circulation ischemic stroke outcome, as described in this article published in Epilepsia Open . Furthermore, because the gold standard of acute stroke care (namely intravenous alteplase treatment) is associated with a reduction of mortality and incapacity of treated patients with possible consequences in poststroke seizure frequency, but a proconvulsive and an epileptogenic effect of alteplase has also been described, we aim to test the hypothesis that ischemic stroke patients treated with intravenous alteplase have a different frequency of epileptic (clinic and/or electroencephalographic) manifestations compared to nontreated patients .…”
Section: What Next Steps In Epilepsy Research Are You Taking and Whatmentioning
confidence: 99%